The Mission and Saving Purpose of God in the Torah: A Canonical-Theological Foundation for Old Testament Mission - Pada, Ellyazer (PT ARRUS Intelektual Indonesia, 2025)
Contemporary mission theology has largely privileged New Testament paradigms, often marginalizing the Torah as merely a legal or historical precursor rather than a theological witness to God’s redemptive mission. This study seeks to address that imbalance by examining the Torah as a foundational and coherent articulation of missio Dei within Old Testament theology. The purpose of this research is to demonstrate that the Pentateuch, read in its final canonical form, embodies a consistent missional logic rooted in God’s creative purpose, covenantal initiative, and redemptive engagement with humanity. Employing a qualitative theological method grounded in canonical and narrative analysis, this study analyzes the theological movement of the Torah from creation and fall to promise, election, liberation, law, wilderness formation, and covenant renewal. The findings reveal that mission in the Torah is not expressed primarily through explicit sending commands but through narrative patterns that portray God as the initiating subject of mission and Israel as a covenant people formed for the sake of the nations. Mission emerges as universal in scope, ethical in expression, and formative in process, sustained by divine faithfulness rather than human consistency. The study concludes that the Torah is constitutive, not merely anticipatory, of biblical mission theology and provides the theological framework upon which later canonical developments build. This research contributes to contemporary missiology by offering a canonically grounded Old Testament foundation for understanding Christian mission as participation in God’s redemptive work from creation onward.